Adverse impact of multiple separations or loss of primary caregivers on young children. Issue 1 (31st December 2019) - Briggs-Gowan, Margaret J.; Greene, Carolyn; Ford, Julian; Clark, Roseanne; McCarthy, Kimberly J.; Carter, Alice S.
ABSTRACT: Background : Young children may be adversely impacted by separation from and loss of caregivers and other loved ones. Such experiences often co-occur with interpersonal violence, unpredictability and other traumas. Whether separation/loss has unique effects independent of those other adversities is not known. Objective : This study aimed to establish whether separation/loss is associated with trauma-related symptoms, psychiatric disorders, and functional impairment in 18- to 48-month-old children independent of other adversities. Methods : Data from a cross-sectional community and clinical cohort were analyzed. Recruitment occurred in pediatric primary care, mental health, and developmental services sites. Children (33% female) were heterogeneous in ethnic background (55% minority) and family socioeconomic status (40% living in poverty). Results : Separation/loss was common (30.9% single type, 15.0% multiple types) and frequent amongst violence-exposed children (84.4% of violence-exposed children had experienced separation/loss from a loved one). However, violence exposure was uncommon amongst children with separation/loss experiences (only 23.9% were violence-exposed). Separation/loss was significantly associated with symptoms of posttraumatic stress and reactive attachment, as well as impairment and psychiatric disorders in models that controlled for sociodemographic and contextual risks, including other traumas. Psychiatric disorders were approximately 2.5 times more likely in children who had experienced multiple separations/losses, after accounting for interpersonal violence which was also significant. Conclusion : Professionals working with young children, policy-makers and caregivers should be aware that an accumulation of caregiver separations/losses, irrespective of violence and other traumatic exposure, may have detrimental effects on young children especially in the context of prior separations/losses or disruptions in their lives. HIGHLIGHTS: Findings link multiple separations from or losses of primary caregivers and other loved ones with trauma-related symptoms, reactive attachment symptoms, impairment, and psychiatric disorders in 18–48 month-olds. Associations are independent of the effects of interpersonal violence and other traumas. Routine screening may be warranted to identify young children who have experienced multiple separations/losses and are manifesting enduring symptoms that merit referral to mental health professionals for further evaluation of the need for trauma-informed therapeutic services.